Economic evaluation of non-invasive test pathways for high-risk metabolic dysfunction-associated steatotic liver disease (MASLD) in the United Kingdom (UK) - Zobair M. Younossi; James M. Paik; Linda Henry; Richard F. Pollock; Maria Stepanova; Fatema Nader (Annals of Hepatology)
Introduction and Objectives: Non-invasive tests (NITs) identifying high-risk MASLD in primary care is suggested but, these strategies cost-effectiveness remain uncertain in the United Kingdom (UK). Materials and Methods: A cost-utility/budget impact model was developed for cost-effectiveness evaluation of two screening strategies (1) FIB-4 followed by Enhanced Liver Fibrosis (ELF) (FIB-4/ELF); (2) FIB-4 followed by Transient Elastography (FIB-4/TE) compared to standard of care (SoC). A cohort of primary care MASLD patients with an advanced fibrosis prevalence of 4.20 % was simulated. A decision tree classified patients as true positives, false positives, true negatives, or false negatives based on NIT diagnostic accuracy, followed by a 3-year Markov model to estimate costs and quality-adjusted life years (QALYs). The model included 11 health states: MASLD, fibrosis stages (F0–F3), cirrhosis, decompensated cirrhosis, liver transplant, and death. Costs came from the National Tariff, National Schedule of Costs and Personal Social Services Research Unit. Results: SoC had a false diagnosis rate of 36.26 %, while FIB-4 with ELF or TE reduced false positive rates to 23.20 % and 20.91 %, respectively. Compared to 112,807 unnecessary hepatology referrals under SoC, FIB-4/ELF or FIB-4/TE reduced unnecessary referrals by 38,031 (33.71 %) and 45,767 (40.57 %), respectively. Both strategies demonstrated cost-effectiveness relative to SoC with total cost per patient of GBP 983.37 for FIB-4/TE, GBP 993.15 for FIB-4/ELF compared to SoC, GBP 1,014.15. Conclusions: Sequential NIT screening strategies, combining FIB-4 with ELF or TE, are cost-saving, reduce unnecessary hepatology referrals, and offer an efficient (improve outcomes and reduce healthcare costs) approach for managing high-risk MASLD in UK primary care.